Diagnostic value of galectin-3 level in patients with hypertrophic cardiomyopathy - Samaouil, Daghar (ScienceRise: Medical Science, 2017)
The aim of the present research was to study galectin-3 level in patients with hypertrophic cardiomyopathy depending on the disease clinical course, the presence of complications and comorbidity for determination of possibilities of its use as hypertrophic cardiomyopathy biomarker. Methods. Galectin-3 level was studied in 90 patients with hypertrophic cardiomyopathy with the analysis depending on the disease clinical course, the presence of complications and comorbidity, as well as in 20 patients with cardiac hypertrophy caused by hypertension as the control group. Results. Galectin-3 level in patients with hypertrophic cardiomyopathy is rather variable and reliably depends on the patients’ age, heart failure severity, and the presence of concomitant third degree hypertension. Besides, there is a tendency to increase galectin-3 level in the presence of atrial fibrillation and after previous myocardial infarction. The correlation between galectin-3 level and hypertrophic cardiomyopathy clinical course peculiarities, the presence of complications and comorbidity points to the limited ability to isolated use of this biomarker for hypertrophic cardiomyopathy diagnostics, but it can be useful for determination of the disease severity and its prognosis. Conclusion. Galectin-3 level variability indicates the given biomarker’s low diagnostic importance in patients with hypertrophic cardiomyopathy, but its dependence on the disease severity indexes shows galectin-3 predictive value in the mentioned group of patients The aim of the present research was to study galectin-3 level in patients with hypertrophic cardiomyopathy depending on the disease clinical course, the presence of complications and comorbidity for determination of possibilities of its use as hypertrophic cardiomyopathy biomarker. Methods. Galectin-3 level was studied in 90 patients with hypertrophic cardiomyopathy with the analysis depending on the disease clinical course, the presence of complications and comorbidity, as well as in 20 patients with cardiac hypertrophy caused by hypertension as the control group. Results. Galectin-3 level in patients with hypertrophic cardiomyopathy is rather variable and reliably depends on the patients’ age, heart failure severity, and the presence of concomitant third degree hypertension. Besides, there is a tendency to increase galectin-3 level in the presence of atrial fibrillation and after previous myocardial infarction. The correlation between galectin-3 level and hypertrophic cardiomyopathy clinical course peculiarities, the presence of complications and comorbidity points to the limited ability to isolated use of this biomarker for hypertrophic cardiomyopathy diagnostics, but it can be useful for determination of the disease severity and its prognosis. Conclusion. Galectin-3 level variability indicates the given biomarker’s low diagnostic importance in patients with hypertrophic cardiomyopathy, but its dependence on the disease severity indexes shows galectin-3 predictive value in the mentioned group of patients